Evaluating the Impact of a Comprehensive Canadian Science-Art Residency Program on the Participating Scientist, Artist and the Public - Lau, Catherine; Barriault, Chantal; Krolik, Julia (Frontiers in Education, 2022)
Science-art residencies can provide opportunities for insightful cross-disciplinary collaborations, science communication, and engagement with the general public. Currently, there are few formal ways for artists and scientists to collaborate in Canada, and even fewer publications on how these experiences can impact learning in informal settings. Art the Science (a Canadian non-profit organization facilitating cross-disciplinary relationships between artists and scientists) piloted a comprehensive multiphase science-art residency program. Phase 1 informed the artist’s work through a full-time experience in a scientific laboratory at an academic institution, Phase 2 showcased the artist’s final artwork, Between the Sand at an off-campus local community event, and Phase 3 published an interactive online version of the work for global distribution. Residency evaluation in each phase was conducted through the use of qualitative and quantitative methods, including interviews, concept mapping, video diaries, and surveys. The artist, scientist and lab members gained new perspectives and inspiration about their respective fields. The artist was able to incorporate theories and processes from the research group into their artistic practice. On the other hand, the scientist saw renewed enthusiasm and curiosity within their research lab, and the lab members reported new ways of thinking about how to communicate their research. Both exhibitions proved to be engaging informal learning experiences for 66.2% of survey participants. The major learning themes included the scientific research and the value of art and science in public engagement. Despite promoting both events as artwork exhibitions, 79.2% of survey participants considered Between the Sand as both an artwork and a science communication product suggesting that science-based art may have the potential to communicate science, even when it is not presented as a science communication effort. Public responses revealed that public perception of funding is not skewed to either discipline and instead seems to call upon both science and arts grants to fund such interdisciplinary initiatives. Providing comprehensive artist residencies in science labs can have a valuable impact on everyone involved: the artist, the research group, and the public.